Towards effective industrial policy in the Western Balkans - Branimir Jovanović; Nina Vujanović (The Vienna Institute for International Economic Studies (wiiw), 2023)
Industrial policy has been largely overlooked in the Western Balkans for the past three decades. However, the region's economic struggles and the adoption of smart specialisation strategies have led to renewed interest in the topic. Promising industrial sectors in the Western Balkans include agri-food, textiles, automotive, energy, IT and tourism. The agri-food industry should aim for premium goods, the textile sector for high-quality final products, the automotive industry for advanced technologies, the energy sector for renewable energy, the tourism industry for unique alternative experiences and the IT industry for fostering greater innovation. The EU and Austria can play a valuable role in supporting the industrial policies of the Western Balkan countries. The EU can provide technical assistance and funding for the implementation of smart specialisation strategies. Austria can contribute its expertise to the development and implementation of specific industrial measures, promote the use of its social partnership model, and share its experience with the dual education system.
Keywords: L50; L60; L80; O10; 330; Industrial policy; Western Balkans; smart specialisation; development